Digital Literacy in Education: An Analysis of Critical Thinking Culture for Preventing the Hoaxes - Nurfazri, Muhammad; Irwansyah, Ferli Septi; Lukman, Fahmy; Ruhullah, Mohammad Eisa; Marinda, Sri Mellia (UIN Sunan Gunung Djati Bandung, 2024)
In the 21st century, a hoax is one of the biggest problems in the world, especially in Indonesia. The post-truth phenomenon and the ease of disseminating information on social media are the primary triggers for this case. Moreover, this disruption era is marked by a flood of information, rapid change, and high use of internet technology. This research intends to analyze the importance of digital literacy, especially critical thinking (CT) culture, in preventing hoax news. A literature review is employed in this research. This method explains how CT skills can be used in digital literacy. The results underscore several points: a) the urgency of digital literacy is based on a big problem in the digital world in Indonesia, namely hoaxes; b) digital literacy can be applied in tips such as those discussed by Facione (1998) regarding the six CT skills that require technical and theoretical skills; c) emphasize technical skills in assessing account identities or media that produce information by Nagler (2017); and d) there are several opportunities for implementing digital literacy. Hence, this research concludes the importance of instilling CT skills in fighting hoax news or misinformation. Apart from that, if we look at the data regarding the low level of digital literacy in Indonesian society, it is urgent to implement digital literacy methods and CT skills integrated with educational institutions or more formal policies.